The philosophy of higher education - Isahak, Aldila (IIUM Press, 2009)
Introduction : The philosophy of higher education is about the empowerment of human beings so as to fully realise their potentials as rational beings. The reason is because the contributions which these individuals can give towards the development of the society are invaluable for the stability and progress of a country. The reason is simply because a nation that is heterogeneous can only be progressive and live in harmony if it has a society that shares common goals and aspirations. This leads one to conclude that a state can achieve its goal when its four components; territory, government, population and sovereignty reinforce one another. This in turn would mean that the government and the people understand their responsibilities in ensuring their territory and sovereignty are properly guarded hence the honour of their countries will be protected. On the otber hand, if these four components of a state are in conflict with one another then social unrests will take place and the state will be stagnant. Since it is said that the pbilosophy of higber education is to empower human beings, one can make an assumption that the importance of having a philosophy of higher education will determine the behaviours of the people of a state.